2020
DOI: 10.1007/s11302-020-09718-x
|View full text |Cite
|
Sign up to set email alerts
|

P2X3 receptors contribute to transition from acute to chronic muscle pain

Abstract: This study aimed to evaluate whether the development and/or maintenance of chronic-latent muscle hyperalgesia is modulated by P2X3 receptors. We also evaluate the expression of P2X3 receptors and PKCε of dorsal root ganglions during these processes. A mouse model of chronic-latent muscle hyperalgesia, induced by carrageenan and evidenced by PGE 2 , was used. Mechanical muscle hyperalgesia was measured by Randall-Selitto analgesimeter. The involvement of P2X3 receptors was analyzed by using the selective P2X3 r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 48 publications
(68 reference statements)
0
3
0
Order By: Relevance
“…Specific targeting of the P2X 3 receptor by genetic deletion and knockdown results in a hypoalgesic phenotype ( Butler and Meegan, 2008 ). Studies have shown that the pharmacological blockade of P2X 3 receptors completely blocked specific types of chronic inflammatory and neuropathic pain ( Kaan et al, 2010 ; Xu et al, 2012 ; Jorge et al, 2020 ). Peripheral nerve injury differentially alters the functional expression of P2X 3 receptors in small- and large-diameter primary afferent neurons ( Inoue, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Specific targeting of the P2X 3 receptor by genetic deletion and knockdown results in a hypoalgesic phenotype ( Butler and Meegan, 2008 ). Studies have shown that the pharmacological blockade of P2X 3 receptors completely blocked specific types of chronic inflammatory and neuropathic pain ( Kaan et al, 2010 ; Xu et al, 2012 ; Jorge et al, 2020 ). Peripheral nerve injury differentially alters the functional expression of P2X 3 receptors in small- and large-diameter primary afferent neurons ( Inoue, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…In particular, activation of the homomeric P2X3 and P2X2/3 receptors in sensory neurons have been associated with acute pain behaviors [ 17 19 ]. For example, blocking P2X3 receptors with the selective P2X3 receptor antagonist A-317491 prevented acute muscle hyperalgesia, but had no effect on chronic-muscle pain [ 18 ]. Conversely, the activation and upregulation of P2X4 receptors on glial cells (i.e., microglia) are linked to the pathogenesis and development of neuropathic pain and mechanical allodynia, thus representing a pathway promoting the development of chronic pain [ 20 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…21 PKC Ɛ mediates latent sensitization of inflammatory pain and contributes to chronification of muscle pain. 1,23 TRPM3 acts upstream of TRPV1 to drive DRG neuronal hyperexcitability. 38 Therefore, mitoflash outbreak may promote TRPV1 sensitivity via PKC Ɛ pathway, thereby contributing to TRPM3-mediated latent sensitization (Fig.…”
Section: Discussionmentioning
confidence: 99%